2019
DOI: 10.1016/j.tate.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Approximations in English language arts: Scaffolding a shared teaching practice

Abstract: Recent research highlights the importance of providing teacher candidates with opportunities to approximate practice. Less attention focuses on tools teacher educators use within and surrounding approximations to focus candidates’ attention on features of practice. This multi-case study investigates how three teacher educators use different approximations in ways that strategically reduce the complexity of learning to teach and scaffold the development of practice. Data indicate teacher educators capitalized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 17 publications
(33 reference statements)
1
6
0
3
Order By: Relevance
“…We found that rehearsals provided rich spaces for working on content. We believe our findings contribute to and extend the growing body of literature on rehearsals in practice-based teacher education (e.g., Kavanagh et al., 2019; Lampert et al., 2013a, 2013b; Schutz, Danielson, & Cohen, 2019) by offering examples in which TEs entwine work on practice with content. Moreover, that TEs in this study conceptualized content knowledge to include interpretive disciplinary practices so that such ways of thinking might be worked on in whole-class discussions, suggests the value of using core instructional practices to engage students in high-level subject matter learning (Grossman et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…We found that rehearsals provided rich spaces for working on content. We believe our findings contribute to and extend the growing body of literature on rehearsals in practice-based teacher education (e.g., Kavanagh et al., 2019; Lampert et al., 2013a, 2013b; Schutz, Danielson, & Cohen, 2019) by offering examples in which TEs entwine work on practice with content. Moreover, that TEs in this study conceptualized content knowledge to include interpretive disciplinary practices so that such ways of thinking might be worked on in whole-class discussions, suggests the value of using core instructional practices to engage students in high-level subject matter learning (Grossman et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…Teachers need support in developing their capacity at this kind of teaching practice (McDonald, Kazemi, & Kavanagh, 2013). This need for support places a burden on teacher educators to design meaningful opportunities to approximate teaching in settings of reduced complexity (Lampert et al, 2013; Schutz et al, 2019). To further reveal what it entails to offer teachers opportunities to approximate practice, in the following section we unpack our conceptualizations of the concepts of both practice and approximations of practice.…”
Section: Responsive Teachingmentioning
confidence: 99%
“…Although there is a community of scholars investigating how teacher educators design and facilitate approximations of teaching, research is still emergent. To date, scholars have investigated variations in how teacher educators structure and facilitate approximations across contexts (Schutz et al, 2019), what novices have opportunities to learn during approximations (Lampert et al, 2013), how teacher educators work on content with novices during approximations (Ghousseini, 2017), and how the culture of a learning community influences approximations (Kazemi, Ghousseini, Cunard, & Turrou, 2016). Some research also suggests that, when paired with other PBTE pedagogies, approximations of teaching exact some influence on what novice teachers do with K-12 students (Kavanagh & Rainey, 2017; Reisman et al, in press).…”
Section: The History Of Practicing Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher educators (TEs) have also begun attempting novel approaches to deliberate practice (Ericsson, 2002(Ericsson, , 2006 by facilitating rehearsals of teaching. In rehearsals, novice teachers enact episodes of teaching as their peers play students and TEs pause the action to provide feedback and discuss instructional choices (Kavanagh et al, 2019;Lampert et al, 2013;Schutz, Danielson, & Cohen, 2019). Additionally, many programs are engaging in significantly more work with video.…”
mentioning
confidence: 99%